2022
DOI: 10.1002/jat.4309
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐34a‐5p as a promising early circulating preclinical biomarker of doxorubicin‐induced chronic cardiotoxicity

Abstract: Cardiotoxicity is a serious adverse effect of an anticancer drug, doxorubicin (DOX), which can occur within a year or decades after completion of therapy. The present study was designed to address a knowledge gap concerning a lack of circulating biomarkers capable of predicting the risk of cardiotoxicity induced by DOX. Profiling of 2083 microRNAs (miRNAs) in mouse plasma revealed 81 differentially expressed miRNAs 1 week after 6, 9, 12, 18, or 24 mg/kg total cumulative DOX doses (earlyonset model) or saline (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Most studies have focused on dynamic changes in cmiRNA after treatment. In all mouse studies, an increase in miR-34a levels was observed in both plasma 37 , 38 , 39 , 40 and myocardial tissue, suggesting a cardiac origin. 37 , 38 Similarly, rats exposed to repeated low doses of DOX showed increased miR-34a levels.…”
Section: Circulating Mirna In Response To Anthracyclines In Animal Mo...mentioning
confidence: 77%
See 3 more Smart Citations
“…Most studies have focused on dynamic changes in cmiRNA after treatment. In all mouse studies, an increase in miR-34a levels was observed in both plasma 37 , 38 , 39 , 40 and myocardial tissue, suggesting a cardiac origin. 37 , 38 Similarly, rats exposed to repeated low doses of DOX showed increased miR-34a levels.…”
Section: Circulating Mirna In Response To Anthracyclines In Animal Mo...mentioning
confidence: 77%
“… 39 , 40 In close association with miR-34a, a rise in miR-34c levels after DOX treatment was also described. 39 , 40 Additionally, an increase in miR-133a levels was observed after DOX treatment in both mice and rats. 37 , 38 , 42 , 43 In rats, an early rise in miR-1 and miR-133b levels was seen in the first 24 hours after a single high dose of anthracyclines.…”
Section: Circulating Mirna In Response To Anthracyclines In Animal Mo...mentioning
confidence: 87%
See 2 more Smart Citations
“…Comparatively, the in vitro study showed that the expressions of miR-34a-5p, miR-34b-3p, and miR-34c-5p were all upregulated. Desai et al [ 132 ] explored the expression of miR-34a-5p by modeling early-onset and late-onset cardiotoxicity using DOX. After one week of treatment with DOX in the early-onset model, only the expression of miR-34a-5p was increased (false discovery rate (FDR) < 0.1), and there were statistically significant dose-related reactions with all the total cumulative doses.…”
Section: Mirna As a Biomarker Of Dicmentioning
confidence: 99%